Cognitive Behavioral Counseling Using Systematic Desensitization Techniques to Reduce Anxiety in High School Students - Ida Ayu Yadnyautami Mahadewi; Putu Ari Dharmayanti; Kadek Ari Dwiarwati (Department of Guidance and Counseling, FIP, Undiksha, 2026)
This research is motivated by the high level of learning anxiety experienced by high school students, which has a negative impact on the learning process and outcomes. Learning anxiety arises due to irrational thinking patterns, academic pressure, and students' inability to manage emotional responses adaptively. This study aims to describe the effectiveness of cognitive behavioral counseling with systematic desensitization techniques in minimizing students' learning anxiety in high school. This research uses a quantitative research approach using a Quasi-Experimental Design (Quasi-Experimental) approach. The type of research used is Nonequivalent Pretest-Posttest Control Group Design. The population used is grade X looking for students who have the highest learning anxiety so that sampling uses Purposive Sampling by getting 9 students who have high learning anxiety as an experimental class and getting 9 students who have moderate learning anxiety as a control class. Data analysis techniques use statistical tests to determine differences in anxiety levels before and after treatment. The results of the study showed a significant decrease in learning anxiety after students participated in counseling. The implications of this study indicate that cognitive behavioral counseling with systematic desensitization techniques is effective and can be applied as an alternative guidance and counseling service in high school.